THE EFFORTS OF SOCIAL SERVICES AND POVERTY TREATMENT IN ADDRESSING STREET CHILDREN IN BANDUNG CITY - Nuradhawati, Rira (Department of Government, FISIP, Universitas Padjadjaran, 2020)
Living as street children is not a pleasant choice, because they are in conditions with no clear future, and their existence often becomes a